Report of the international conference on regulatory endeavors towards the sound development of human cell therapy products. Issue 5 (September 2015) - Hayakawa, Takao; Aoi, Takashi; Bravery, Christopher; Hoogendoorn, Karin; Knezevic, Ivana; Koga, Junichi; Maeda, Daisuke; Matsuyama, Akifumi; McBlane, James; Morio, Tomohiro; Petricciani, John; Rao, Mahendra; et al.
Abstract The regulation of human cell therapy products is a key factor in their development and use to treat human diseases. In that regard, there is a recognized need for a global effort to develop a set of common principles that may serve to facilitate a convergence of regulatory approaches to ensure the smooth and efficient evaluation of products. This conference, with experts from regulatory agencies, industry, and academia, contributed to the process of developing such a document. Elements that could form a minimum consensus package of requirements for evaluating human cell therapy products were the overall focus of the conference. The important regulatory considerations that are unique to human cell therapy products were highlighted. Sessions addressed specific points that are different from those of traditional biological/biotechnological protein products. Panel discussions complemented the presentations. The conference concluded that most of the current regulatory framework is appropriate for cell therapy, but there are some areas where the application of the requirements for traditional biologicals is inappropriate. In addition, it was agreed that there is a need for international consensus on core regulatory elements, and that one of the major international organizations should take the lead in formulating such a consensus document.